Dansk bogfortegnelse.
Some vols. have title page in English. The Danish national bibliography, books, consists of four parts: the weekly list is published in the journal Det Danske bogmarked and has only an alphabetical section; the monthly list, Manedsfortegnelsen; the annual list, Årskatalog, which includes the Faroese bibliography, The Greenland bibliography, and the Danish bibliography of maps; the multi-annual lists, Flerarige kataloger, with the same contents as the annual. Vols. for 1915-19 -1930-34 include Islandsk bogfortegnelse for the same dates. Vol. for 1841-58 is a photocopy. Mode of access: Internet. Deacidified. Rebound.